2022
DOI: 10.3389/fimmu.2022.841868
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of BCG Revaccination With M. bovis BCG Moscow to Prevent COVID-19 Infection in Health Care Workers: A Randomized Phase II Clinical Trial

Abstract: The Bacillus Calmette-Guérin (BCG) vaccine, which is widely used to protect children against tuberculosis, can also improve immune response against viral infections. This unicentric, randomized-controlled clinical trial assessed the efficacy and safety of revaccination with BCG Moscow in reducing the positivity and symptoms of COVID-19 in health care workers (HCWs) during the COVID-19 pandemic. HCWs who had negative COVID-19 IgM and IgG and who dedicated at least eight hours per week in facilities that attende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 46 publications
2
61
0
Order By: Relevance
“…However, the little apparent pathology, the low circulating cytokine levels, and the bacterial loads at or below the limit of detection are consistent with our unpublished work in BCG-vaccinated C57BL/6 mice. Other studies have shown that recombinant BCG vaccination in mice ( 30 ), revaccination with BCG in a clinical trial ( 31 ), and other routes of vaccination (intravenous) affect SARS-CoV-2 morbidity and mortality ( 26 ), demonstrating BCG’s unique off-target effects and potential as an adjuvant or booster. However, our study attempted to best experimentally represent what BCG’s effect would be clinically on SARS-CoV-2 given current vaccination regimens, which are intradermal and given at birth.…”
Section: Discussionmentioning
confidence: 99%
“…However, the little apparent pathology, the low circulating cytokine levels, and the bacterial loads at or below the limit of detection are consistent with our unpublished work in BCG-vaccinated C57BL/6 mice. Other studies have shown that recombinant BCG vaccination in mice ( 30 ), revaccination with BCG in a clinical trial ( 31 ), and other routes of vaccination (intravenous) affect SARS-CoV-2 morbidity and mortality ( 26 ), demonstrating BCG’s unique off-target effects and potential as an adjuvant or booster. However, our study attempted to best experimentally represent what BCG’s effect would be clinically on SARS-CoV-2 given current vaccination regimens, which are intradermal and given at birth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was a trend towards reduced incidence of severe infections in the BCG arm. A single-centre phase II randomised control trial involving healthcare workers at high risk of COVID-19 infection in Brazil has shown a trend towards a reduction in the incidence of COVID-19 infection in those vaccinated with BCG [ 16 ]. In a multi-centre randomised double-blind trial conducted across three facilities in West Cape South Africa which included 1000 healthcare workers who received either BCG vaccination or placebo, there was no significant difference between the two groups in terms of COVID-19 incidence or hospitalisation due to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Nine (60%) trials were conducted in healthy individuals, two (13%) included participants with various comorbidities, and four (27%) were done in low-birth-weight children (<2500g). The primary objectives of 14 (93%) trials [4–8,15,23,25–31] was to evaluate BCG-mediated NSE on mortality, infections of any origin, and respiratory infections; four (27%) trials [15,26,27,31] specifically investigated BCG-mediated NSE on COVID-19; one (7%) trial [24] was conducted to study prevention of M. tuberculosis infection with BCG revaccination. As intervention the BCG Denmark strain was used in ten (67%) trials; one (7%) trial used the BCG Glaxo-strain which is genetically close to the BCG Denmark strain; two trials used the BCG Moscow strain; the remaining two trials used the strains BCG Paris or BCG Russia respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Three of them were conducted in healthy newborns (weight 43.8%) [7,8,23], one in adolescents who already received BCG in infancy (weight 18%) [24], one in adults (weight 19.5%) [26], and three in elderly with unknown previous BCG exposure (weight 23.6%) [15,27,28]. Combined HRs from random-effects meta-analyses indicated a beneficial effect of the vaccine on non-tuberculosis respiratory infections (HR 0.51, 95% CI 0.33-0.80); heterogeneity between trials was substantial (I 2 =80%; p<0.00001) (Fig 2A).…”
Section: Resultsmentioning
confidence: 99%